2019
DOI: 10.2147/ijn.s184911
|View full text |Cite
|
Sign up to set email alerts
|

Designing and enhancing the antifungal activity of corneal specific cell penetrating peptide using gelatin hydrogel delivery system

Abstract: BackgroundFungal keratitis is a major cause of corneal blindness accounting for more than one-third of microbiologically proven cases. The management of fungal keratitis is through topical or systemic antifungal medications alone or in combination with surgical treatment. Topical medications such as natamycin and voriconazole pose major challenges due to poor penetration across the corneal epithelium. To address the issue various carrier molecules like nanoparticles, lipid vesicles, and cell penetrating peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…In addition, Ramachandran plot was used to further verify the accuracy of the structure. 25,26 The plot showed that more than 97% of residues were located in spatially allowed region ( Fig. S2 †).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, Ramachandran plot was used to further verify the accuracy of the structure. 25,26 The plot showed that more than 97% of residues were located in spatially allowed region ( Fig. S2 †).…”
Section: Resultsmentioning
confidence: 98%
“…The optimum temperature of the enzyme was determined by incubation of the reaction mixture (the enzymatic-activity assay system) at 15,20,25,26,28,30,35,40,45, or 50 C. The optimum pH of the enzyme was determined using 100 mM Tris-HCl with adjustment of buffer pH from 6 to 10 in 0.5-unit steps. The maximum enzymatic activity, which was achieved at the optimum temperature and pH, was set to 100%.…”
Section: Ak Activity and Steady-state Kinetics Assaysmentioning
confidence: 99%
“…Significant differences have been observed in all the cases (p < 0.05). The aforementioned results could be explained by the mucoadhesive properties of gelatin, leading to a higher retention time on the ocular surface [48] and higher corneal penetration of the nanoparticulate system [47,51,83]. These data demonstrate that timolol loaded gelatin nanoparticles can result in a very promising strategy for ocular delivery of hypotensive compounds and that, interestingly, target pressure can be modulated employing different concentrations of TM-GNP.…”
Section: Discussionmentioning
confidence: 79%
“…50 mg/ml of gelatin concentration with 0.8 µg/mL of glutaraldehyde as crosslinker were used for preparing hydrogel and incubated at 4 °C for 4 h for gelation and cross-linking. The cross-linked gelatin hydrogels were immersed in a 50 mM glycine aqueous solution under agitation for 1 h to block the residual aldehyde groups of glutaraldehyde, followed by two washes with double-distilled water for 1 h 43 . The stiffness of the hydrogels were measured using Microsquischer (M/s.Cell Scale) instrument.…”
Section: Sds Page and In-gel Digestionmentioning
confidence: 99%